Analysis of Determinant Factors Performance of Alliance Strategy: Empirical Study in Learning Guidance in DKI Jakarta - Maikel Rudianto; Unggul Purwohedi; Budi Santoso (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
The alliance strategy is one solution to face the speed of competition in the business world or business. Strategic alliances are cooperative strategies in the form of partnerships that help bring together the strengths of each party in order to benefit each other in the form of long-term benefits and competitiveness in the market. The Alliance strategy can be judged successful or not by measuring the performance of the strategic alliance, because the most commonly used alliance measure is performance. So that a healthy alliance strategy implemented by a company is to see and evaluate the performance of the company's alliance strategy.This research was conducted with a non-sampling method or census of 132 (one hundred thirty-two) branches in DKI Jakarta in one of the companies in the field of education originating from Japan and developing an alliance strategy in Indonesia. Data collection is done by questionnaire and meet with the owners or branch leaders directlyFrom this study it was concluded that Goodwill trust, Competence Trust and Tangible & Intangible Resources Sharing had a positive influence on the performance of the alliance's strategy. Besides Tangible & Intangible Resources Sharing as an intervening variable is able to mediate the relationship of Goodwill trust and Competence Trust on the performance of the alliance's strategy.